2015
DOI: 10.1007/s12182-015-0016-y
|View full text |Cite
|
Sign up to set email alerts
|

Liquid marbles containing petroleum and their properties

Abstract: Liquid marbles (non-stick droplets) containing crude petroleum are reported. Liquid marbles were obtained by use of fluorinated decyl polyhedral oligomeric silsequioxane (FD-POSS) powder. Marbles containing crude petroleum remained stable on a broad diversity of solid and liquid supports. The effective surface tension of marbles filled with petroleum was established. The mechanism of friction of the marbles is discussed. Actuation of liquid marbles containing crude petroleum with an electric field is presented. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…By using electrostatic interactions, it was also showed that a liquid droplet can be spontaneously coated with hydrophobic particles, resulting in multi‐layered LM . By exposing LM to an electric field provided by a capacitor, LM could be actively deformed and controlled their movements . Similar behavior was also reported for “Janus” marbles, which are droplets composed of two hemispheres characterized by presenting different physical and/or chemical properties.…”
Section: Liquid Marblesmentioning
confidence: 58%
See 1 more Smart Citation
“…By using electrostatic interactions, it was also showed that a liquid droplet can be spontaneously coated with hydrophobic particles, resulting in multi‐layered LM . By exposing LM to an electric field provided by a capacitor, LM could be actively deformed and controlled their movements . Similar behavior was also reported for “Janus” marbles, which are droplets composed of two hemispheres characterized by presenting different physical and/or chemical properties.…”
Section: Liquid Marblesmentioning
confidence: 58%
“…It was showed that LM can also be deformed, moved and can experience changes in their wettability when exposed to an electric field . Aussillous and Quéré showed for the first time that LM can be moved by the effect of an electrostatic field, where this field was reached by simply rubbing a stick of Teflon on a fabric .…”
Section: Liquid Marblesmentioning
confidence: 99%
“…The Bormashenko group has investigated the effect of an electric field on liquid marble shape and motion using an experimental apparatus to apply an electric field in a well‐defined manner . They demonstrated that a PVDF‐particle‐stabilized water marble placed on a glass slide could be stretched in the vertical direction in a uniform vertically applied electric field .…”
Section: Stimuli‐responsive Liquid Marblesmentioning
confidence: 99%
“…This microliter droplet is made of water generally (because its high surface tension allows for the easiest LM formation), though glycerol is quite common [4], and even petroleum has been used [7]. This paper will focus on water-filled LMs.…”
Section: Liquid Marblesmentioning
confidence: 99%